Characterization of Kordiimonas marina sp. nov. and Kordiimonas laminariae sp. nov. and Comparative Genomic Analysis of the Genus Kordiimonas, A Marine-Adapted Taxon - Ye, Yu-Qi; Hao, Zhi-Peng; Yue, Yu-Yan; Ma, Lu; Ye, Meng-Qi; Du, Zong-Jun (Frontiers in Marine Science, 2022)
Two novel rod-shaped and Gram-negative bacterial strains, designated A6E486T and 5E331T, were isolated from a coastal sediment sample taken from Xiaoshi Island, Weihai, China, and a fresh kelp sample collected from a kelp culture area, Rongcheng, China, respectively. Growth of strain A6E486T occurred at 20°C–43°C (optimum, 33°C–35°C) at pH 5.5–7.5 (optimum, 6.5) and in the presence of 1.0%–5.5% (w/v) NaCl (optimum, 2.5%–3.0%). Strain 5E331T grew with 1.5%–5.0% (w/v) NaCl (optimum, 3.0%) at 15°C–40°C (optimum, 33°) and pH 6.0–8.5 (optimum, 7.0). The similarity of 16S rRNA gene sequence between the two strains was 95.2%. The phylogenetic analysis based on 16S rRNA gene sequence showed that strains A6E486T and 5E331T belong to the genus Kordiimonas, sharing the highest similarity to the genus Kordiimonas (94.6%–96.8%, 94.9%–96.1%, respectively). Strains A6E486T and 5E331T had percentage of conserved protein (POCP) values of 56.0%–67.3% and average nucleotide identity (ANI) values of 68.8%–73.1% to members of the genus Kordiimonas. The major polar lipids detected in the two strains were phosphatidylethanolamine (PE), phosphatidylglycerol (PG), diphosphatidylglycerol (DPG), and unidentified glycolipids, aminolipids, and lipids. The predominant respiratory quinone of the two strains was Q-10. Based upon the results presented in this study, strains A6E486T and 5E331T represent two novel species of the genus Kordiimonas, for which the names Kordiimonas marina and Kordiimonas laminariae are proposed with the type strains A6E486T (= KCTC 82758T = MCCC 1H00470T) and 5E331T (= KCTC 92199T = MCCC 1H00515T), respectively. Comparative genomic analysis showed that seven species of the genus Kordiimonas shared 1,258 core genes and had differences in carbohydrate metabolism, energy metabolism, and cofactor and vitamin metabolism. The pan-genome of the genus Kordiimonas was open. The prediction of secondary metabolites showed that most strains of the genus Kordiimonas had the ability to produce homoserine lactones, one of the most important signal molecules in the quorum-sensing system of Gram-negative bacteria. Additionally, numerous genes involved in bacterial defense, motility and chemotaxis, cold adaptation, and environment stress response were found in the genus Kordiimonas, indicating the marine-adapted lifestyle of members of the genus Kordiimonas.